2022
DOI: 10.1101/2022.08.10.501131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrotransposons facilitates tissue specific horizontal transfer of circulating tumor DNA between human cells

Abstract: A variety of organisms have been shown to have altered physiology or developed pathology as a result of gene transfer, but mammals has never been shown to do so. Here, we show that circulating tumor DNA (ct) can promote cell-specific horizontal gene transfer (HGT) between human cancer cells and explain the mechanisms behind this phenomenon. Once ctDNA enters the host cell, it migrates to the nucleus and integrate into the cells genome, thereby transferring its genetic information. We determine that retrotransp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 52 publications
(69 reference statements)
1
3
0
Order By: Relevance
“…Direct comparison of MM-ZC with other DNA sequences demonstrated the specific and significant internalization of MM-ZC in MM1R, other widely used myeloma cell lines. This result is similar to that of MM1S cells whose data is present in elsewhere (1) and demonstrated a significant uptake of MM-ZC compared to the other DNA sequences (Figure 2A, compare MM-ZC bar graph with other DNA sequences). Both trypsin-treated and untreated cells showed similar patterns.…”
Section: Evaluation Of Mm-zc Uptake By Different Cell Linessupporting
confidence: 88%
See 3 more Smart Citations
“…Direct comparison of MM-ZC with other DNA sequences demonstrated the specific and significant internalization of MM-ZC in MM1R, other widely used myeloma cell lines. This result is similar to that of MM1S cells whose data is present in elsewhere (1) and demonstrated a significant uptake of MM-ZC compared to the other DNA sequences (Figure 2A, compare MM-ZC bar graph with other DNA sequences). Both trypsin-treated and untreated cells showed similar patterns.…”
Section: Evaluation Of Mm-zc Uptake By Different Cell Linessupporting
confidence: 88%
“…Previously we have demonstrated a significant discovery related to horizontal gene transfer (HGT) in the context of cancer, explicitly involving cell-free DNA circulating tumor DNA (ctDNA) as a vehicle for transferring genes between cancer cells. Our pioneering study revealed that retrotransposons, specific mobile elements within the ctDNA, play a central role in mediating HGT in cancer (1). Retrotransposons are sequences capable of moving within the genome, and their reactivation in cancer cells may facilitate their integration into the cancer cell genome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that ctDNA naturally has an affinity for recipient cells that are phenotypically and genotypically similar to the donor cells. By identifying the DNA sequences at ctDNA insertion sites and demonstrating that synthetically generated transposon sequences can deliver payloads to target cells, therefore, we proved that these zip code sequences play a pivotal role in HGT communication by mediating targeted interactions between donor and recipient cells, facilitating the transfer of genetic material or signaling molecules [ 31 ].…”
Section: Background and Significance Of Gene Transfer (Gt)mentioning
confidence: 99%